Synthesis of manganese vanadate nanobelts and their visible light photocatalytic activity for methylene blue. Issue 3 (11th February 2016) - Pei, L.Z.; Lin, N.; Wei, T.; Yu, H.Y.
Abstract : Manganese vanadate nanobelts have been synthesised by a simple hydrothermal process using polymer polyvinyl pyrrolidone as the surfactant by adjusting the pH value. The X-ray diffraction, selected area electron diffraction and the high-resolution transmission electron microscopy (TEM) show that the manganese vanadate nanobelts are composed of a single crystalline monoclinic Mn2 V2 O7 phase. Scanning electron microscopy and TEM observations show that the thickness, width and length of the nanobelts are 20 nm, 350 nm–1 μm and several dozens to several hundreds of micrometres, respectively. The photocatalytic activities of the manganese vanadate nanobelts have been evaluated by the photocatalytic degradation of methylene blue (MB) in an aqueous solution as a model pollutant under the solar light irradiation. After 4 h of the irradiation by the solar light, the MB solution with the volume of 10 mL and the concentration of 10 mg·mL −1 can be totally degraded using 10 mg manganese vanadate nanobelts.